Imperfect Capital Markets and the Theory of Investment - Foldes, Lucien (Review of Economic Studies, 1961)
Journal Article Imperfect Capital Markets and the Theory of Investment Get access Lucien Foldes Lucien Foldes London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 3, June 1961, Pages 182–195, https://doi.org/10.2307/2295947 Published: 01 June 1961